Modeling a Telemedicine Screening Program for Diabetic Retinopathy in Iran and Implementing a Pilot Project in Tehran Suburb. (4th March 2019) - Safi, Sare; Ahmadieh, Hamid; Katibeh, Marzieh; Yaseri, Mehdi; Nikkhah, Homayoun; Karimi, Saeed; Nourinia, Ramin; Tivay, Ali; Zareinejad, Mohammad; Azarmina, Mohsen; Ramezani, Alireza; Moradian, Siamak; et al.
Abstract : Purpose . To model a community-based telescreening program for diabetic retinopathy (DR) in Iran and to implement a pilot project at the Iranian Diabetes Society (IDS) branch in a Tehran suburb. Methods . In this mixed model study, a web application called the "Iranian Retinopathy Teleophthalmology Screening (IRTOS)" was launched. The educational course for DR screening was established for general practitioners (GPs). Registered patients in IDS branch were recalled for fundus photography; images were transferred to the reading center via IRTOS to be graded by GPs, and patients were informed about the results via mobile messaging. All images were independently reviewed by a retina specialist as the gold standard. Patients who required further assessment were referred to an eye hospital. Results . Overall, 604 subjects with diabetes were screened; of these, 50% required referral. The sensitivity and specificity for diagnosis of any stage of DR by trained GPs were 82.8% and 86.2%, respectively, in comparison to the gold standard. The corresponding values for detecting any stage of diabetic macular edema (DME) were 63.5% and 96.6%, respectively. Conclusions . Telescreening was an effective method for detecting DR in a Tehran suburb. This screening model demonstrated its capacity for promoting diabetic eye care services at the national level. However, the sensitivity for detecting DME needs to be improved by modifying the referral pathway and promoting the skill of GPs.